The Role of Smart Packaging in Improving The Quality and Safety of Bakery Products - Rahayu, Ifnalia; Gusnita, Wiwik; Lofandri, Wiki (Sean Institute, 2025)
The development of packaging technology presents smart packaging innovations that can improve the quality and safety of bakery products. Smart packaging consists of intelligent packaging and active packaging, which can provide real-time information about product conditions and extend shelf life through active interaction with the environment. This article discusses the concept, benefits, and implementation of smart packaging in the bakery industry, highlighting aspects of food safety, product durability, and consumer preferences for this packaging technology. It also reviews the trends and challenges in implementing smart packaging as an innovative solution for the quality-oriented and sustainable bakery industry.